Identification of Clinical Isolates of Actinomyces Species by Amplified 16S Ribosomal DNA Restriction Analysis - Hall, Val (American Society for Microbiology, 2001)
Amplified 16S ribosomal DNA (rDNA) restriction analysis (ARDRA), using enzymes HaeIII and HpaII, was applied to 176 fresh and 299 stored clinical isolates of putative Actinomyces spp. referred to the Anaerobe Reference Unit of the Public Health Laboratory Service for confirmation of identity. Results were compared with ARDRA results obtained previously for reference strains and with conventional phenotypic reactions. Identities of some strains were confirmed by analysis of partial 16S rDNA sequences. Of the 475 isolates, 331 (70%) were clearly assigned to recognized Actinomyces species, including 94 isolates assigned to six recently described species. A further 52 isolates in 12 ARDRA profiles were designated as apparently resembling recognized species, and 44 isolates, in 18 novel profiles, were confirmed as members of genera other than Actinomyces. The identities of 48 isolates in nine profiles remain uncertain, and they may represent novel species of Actinomyces. For the majority of species, phenotypic results, published reactions for the species, and ARDRA profiles concurred. However, of 113 stored isolates originally identified as A. meyeri or resembling A. meyeri by phenotypic tests, only 21 were confirmed as A. meyeri by ARDRA; 63 were reassigned as A. turicensis, 7 as other recognized species, and 22 as unidentified actinomycetes. Analyses of incidence and clinical associations of Actinomyces spp. add to the currently sparse knowledge of some recently described species.